3r-3+12r-8=

Simple and best practice solution for 3r-3+12r-8= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3r-3+12r-8= equation:


Simplifying
3r + -3 + 12r + -8 = 0

Reorder the terms:
-3 + -8 + 3r + 12r = 0

Combine like terms: -3 + -8 = -11
-11 + 3r + 12r = 0

Combine like terms: 3r + 12r = 15r
-11 + 15r = 0

Solving
-11 + 15r = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 15r = 0 + 11

Combine like terms: -11 + 11 = 0
0 + 15r = 0 + 11
15r = 0 + 11

Combine like terms: 0 + 11 = 11
15r = 11

Divide each side by '15'.
r = 0.7333333333

Simplifying
r = 0.7333333333

See similar equations:

| y/3=2=10 | | 39-47=2 | | -7x+8(x-5)=-47+x | | 6(n+7)-7=83 | | 2y-1/7-y-3/6=1/2 | | s+2s+(2s+18)=348 | | a*5-35=70 | | 5.8=475.6/w | | 5n+3=53+3n | | 1+sin^2x+cosx=0 | | a/14=10 | | 8+6(3y-8)=-130 | | 6x^4+14x^3-x^2+5x+3=0 | | -15x+5y=-5 | | y-2=1/2(1x-6) | | 4x-31=5+x | | 2(5a-6)+8a=60 | | Y=-5(-4)-14 | | 4p+10=7(p-4)-4(-2-3p) | | -4=-5x-14 | | 5X^3-5x+1=0 | | -5y-15+9y+22+3y=8-2y+12+4y+33 | | 8+3x=2x+24 | | 12x-3x+11=4x-17+9x | | -7(-x-9)=5(-3x-5) | | 7(d+6)=98 | | F(n)=4.5-50 | | 2f+x+4=64 | | 9i+30-15i=78 | | 2s+7s=7 | | 5r+8+3r-2=118 | | 1/2^6 |

Equations solver categories